Study on Predicting the Gasification Process of Acacia Wood on a Downdraft Gasifier: Using the Non-stoichiometric Equilibrium Model - Nguyen, Thanh Luan; Hoang, An Quoc; Hoang, Duong Hung (Journal of Technical Education Science, 2022)
This study presents a prediction of acacia wood of Vietnam gasification in a downdraft gasifier based on the thermodynamic equilibrium model. Analytical solution for the mathematical model obtained by using an EES (Engineering Equation Solver) program. In the survey, moisture content per mole of biomass MC= 10 ¸ 30%, The ratio of the actual amount of oxygen used for gasification with the amount of oxygen for complete combustion of the biomass ER= 0.21 ¸ 0.4. Results indicated that the lower heating value of syngas decreases with increasing MC or ER. Thermal efficiency tends to increase with rising ER from 0.21 to 0.374, and it will decrease if ER continues to increase. The lower heating value of dry products from 4.51 to 6.51 MJ/nm3, the heat efficiency from 49.62 to 75.53%. The carbon conversion factor tends to increase with an increase as MC or ER. The influence of MC on the carbon conversion factor is insignificant. The content of CO2 and CH4 increased, the content of CO decreased with increased MC or ER. The composition of H2 increases as MC increases while the H2 component increases slightly and then decreases with increasing ER.